Technological change and international relations. (June 2019) - Drezner, Daniel W
This article reflects on the role that technological change has played in the last century on international relations. It makes two main points. First, the relationship is reciprocal; while technological change has undeniable effects on international relations, the changing nature of world politics also affects the pace of technological change. Second, any technological change is also an exercise in economic redistribution and societal disruption. It creates new winners and losers, alters actor preferences, and allows the strategic construction of new norms and organizations. The nature of the technology itself, and the extent to which the public sector drives the innovation, generates differential effects on international relations. To demonstrate these arguments, special emphasis is placed on two important innovations of the last century for international relations: nuclear weapons and the Internet.